Nightlife, Nihilism, and The Existential Crisis of Indonesian Urban Youth: An Islamic and Philosophical Analysis - Abdillah Achmad Al Faruq; Toto Santi Adji; Abdul Muiz; Adang Darmawan Achmad; Qotadah, Hudzaifah Achmad (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
The phenomenon of nightlife among urban youth in Indonesia has shown remarkable escalation in line with the rapid processes of urbanization, modernization, and cultural globalization. Nightlife is no longer merely perceived as a form of leisure or entertainment but has evolved into a medium of recreation, self-expression, identity construction, and social existence. The presence of nightclubs, music concerts, bars, and even digital activities such as nighttime live streaming has become an inseparable element of contemporary urban lifestyles. Nevertheless, behind its popularity, nightlife frequently reflects fundamental problems faced by younger generations, namely nihilism and the crisis of meaning. As described by Friedrich Nietzsche, nihilism signifies a condition in which individuals lose their moral foundations, experience spiritual emptiness, and perceive life as devoid of clear purpose. Within the Indonesian context, this phenomenon has been intensified by increasingly individualistic, fragmented, and pleasure-driven lifestyles, where nightlife often serves as an escape mechanism from social pressures and existential confusion. This article employs a qualitative approach through a literature-based study to examine nightlife within the framework of nihilistic philosophy and Islamic ethics. The analysis highlights three dimensions: (1) the connection between nightlife and hedonistic lifestyles as manifestations of nihilism, (2) the crisis of meaning in urban culture that generates both social alienation and spiritual estrangement, and (3) the proposed solutions offered by Islamic ethics and law, particularly through maqāṣid al-sharī‘ah and Sufi spirituality, to restore moral awareness and meaningful life orientation. The findings suggest that nightlife represents a broader value shift in contemporary urban culture, carrying significant implications for the identity and spirituality of Muslim youth. Therefore, a critical and solution-oriented framework rooted in Islamic ethics is urgently needed to integrate recreational needs with spiritual direction, ensuring that Islamic values remain relevant amidst the challenges of modern urban life.